Gerakan sosial Budha Tzu Chi pasca reformasi di Kota Medan - Rholand Muary; Pujiati Pujiati; Rizabuana Ismail (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This study discusses the social movement conducted by post-reform Tzu Chi organization in Medan. The theory used is theory of social movements with three main factors in social movements; 1) political opportunity structure, 2) collective action frames, and 3) resource mobilization theory. This study aims to a) looking the concept of social movements, b) analyzing the concept of religious movements and c) revealing the position of Tzu Chi in Buddhism. This research applies qualitative methods with direct observation by analyzing subjective and objective experiences in sociological approach. This study was conducted in Medan City due to the following reasons: (1) the diverse population of Medan (2) Tzu Chi has many programs and volunteers in this city. The key informant in this study is the management of structural organization Tzu Chi, as it is considered representative and experienced in the organization. Additional informants are regular volunteers. The results of this study reveals that in the post reform era, Tzu Chi was growing and getting support from the inter-faith and ethnic. Majority ethnic of Tzu Chi is Chinese and form an organization which plays role as a container in showing its identity to maintain social stability and harmony amidst the diverse city of Medan. Their funding network collected through the business network, kinship and spiritual motivation of Buddhist teachings make organizational resources increasingly move to broaden the vision and mission of the organization. In conclusion, in the socio-religious context, Tzu Chi purifications for its Buddhist followers and implements organizational management patterns with 4 in 1 systems which considered modern, minimizing organizational conflicts and able to face the challenges.